(untitled) (Modern American Journal of Medical and Health Sciences, 2026)
Small enterprises play a significant role in ensuring economic stability, employment growth, and regional development in emerging economies. In Uzbekistan, the small business sector has become one of the key drivers of national economic modernization. However, the effectiveness and sustainability of small enterprises largely depend on their ability to adapt to rapidly changing external business conditions. Economic instability, digital transformation, regulatory reforms, market competition, technological change, and globalization create both opportunities and risks for entrepreneurial activity. Therefore, the strategic analysis of external business conditions has become an essential element of sustainable enterprise management. This study examines the major external factors influencing the development and competitiveness of small enterprises in Uzbekistan. The research focuses on the interaction between economic, political, technological, social, legal, and market-related conditions that shape the operational environment of small businesses. The paper proposes an integrated analytical approach for evaluating external business conditions through the combination of strategic management tools, environmental assessment methods, and adaptive business analysis. Particular attention is given to the role of institutional reforms, digitalization processes, state support mechanisms, and investment climate improvements in strengthening entrepreneurial resilience. The methodological basis of the study includes comparative analysis, strategic assessment methods, system analysis, and synthesis of contemporary approaches to business environment evaluation.